Is the prevalence of psychosis in the very old decreasing? A comparison of 85‐year‐olds born 22 years apart. (14th August 2019) - Östling, Svante; Bäckman, Kristoffer; Sigström, Robert; Skoog, Ingmar
Abstract : Objective: To elucidate whether there is a decrease of psychotic symptoms in 85‐years‐olds without dementia and if factors associated with psychotic symptoms have changed, we studied two birth cohorts of 85‐year‐olds born 22 years apart. Methods: Every second, 85‐year‐olds in Gothenburg, Sweden was invited to neuropsychiatric examinations in 1986 to 1987 (participation 63.1%, N = 494) and in 2008 to 2010 (60.5%, N = 571). A close informant was interviewed by a psychiatrist or a research psychologist. Results: The prevalence of psychotic symptoms in 85‐years‐olds without dementia decreased from 10.1% in 1986 to 1987 to 3.2% in 2008 to 2010 ( P < .001). Disability in daily life (odds ratio [OR], 2.3; 95% confidence interval [CI], 1.1‐4.5), depressed mood (OR, 3.9; 95% CI, 2.1‐7.1), irritability (OR, 3.6; 95% CI, 1.2‐10.5), and suicidal ideation (OR, 4.1; 95% CI, 2.1‐8.0) were associated with psychotic symptoms in both cohorts. Mean mini‐mental state examination (MMSE) score was lower in those with psychotic symptom compared with those with no psychotic symptoms (Cohort 1986‐1987, 26.4 vs 27.8, Cohort 2008‐2009, 26.1 vs 27.7, t value −4.24, Pr > t < 0.001). Conclusion: The prevalence of psychotic symptoms decreased between 1986 to 1987 and 2008 to 2010 among 85‐years‐olds without dementia. These symptoms were associated with broad psychopathology, worse performance in cognitive testing, and with disability of daily life in both cohorts.